Thermal properties and degradation of enantiomeric copolyesteramides poly(lactic acid-co-alanine)s. (January 2020) - Tsuji, Hideto; Sato, Shotaro; Masaki, Noriaki; Arakawa, Yuki; Yoshizaki, Yuta; Kuzuya, Akinori; Ohya, Yuichi
Abstract: Thermal properties and degradation of enantiomeric random copolyesteramides poly(l -lactic acid- co -l -alanine) [P(LLA-LAL)] and poly(d -lactic acid- co -d -alanine) [P(DLA-DAL)] copolymers with wide alanine unit content ranges from 0 to 21 and 22 mol% were investigated by differential scanning calorimetry and themogravimetry. The total enthalpy of cold crystallization enthalpy and melting enthalpy as an indicator of crystallinity decreased with a decrease in lactic acid unit content or an increase in alanine unit content. Equilibrium melting temperature values of α-form homo-crystallites for the unblended samples decreased with an increase in alanine unit content (157.3–179.6 °C) and those of δ-form homo-crystallites for the unblended L100 and D100 (190.7 and 185.1 °C) were much higher than the reported values (both 172.8 °C, Polymer 2017, 9, 625). Thermal stability was enhanced by enantiomeric polymer blending, although thermal degradation was accelerated by incorporated alanine units. The activation energy for thermal degradation ( ΔE td ) of the blend samples decreased with an increase in alanine unit content, whereas that of the unblended samples showed complicated dependence on alanine unit content and became maximum at alanine unit contents of 21 and 22 mol%. The blend samples had higher ΔE td values comparted to those of the unblended samples, except for the alanine unit contents of 21 and 22 mol%. The reason for the high ΔE td values of the unblended samples compared with that of the blend sample at the alanine unit contents of 21 and 22 mol% is discussed. Graphical abstract: Image 1 Highlights: Thermal properties and degradation of poly(lactic acid- co -alanine)s are reported in detail. Enantiomeric blending enhances the thermal stability of poly(lactic acid- co -alanine)s. The hydrogen bonding of amide groups plays an important role in thermal degradation.